The Influence of Corporate Social Responsibility Disclosure to Financial Performance on Islamic Banking in Indonesia (Journal of Business and Management, 2022)
The practice of Corporate Social Responsibility (CSR) becomes a substantial matter for Islamic banking concerning their moral obligations. Hence, the practice of CSR Disclosure (CSRD) becomes notable to convince all parties that they truly conduct CSR activities. To see how efficiently a company runs its business, financial performance (FP) is prominent, especially the profitability section. This study aims to examine the influence of CSRD on financial profitability performance in Islamic banking from 2016-2020 with 10 samples Islamic banks in Indonesia. By adopting the CSRD index from a previous study which developed a comprehensive CSRD index and using multiple regression analysis on CSRD index as the independent variable, Non-Performing Financing (NPF), Capital Adequacy Ratio (CAR), and Bank Size as the control variables, also Return on Assets (ROA) as the dependent variable. This study revealed that CSRD has a positive relationship but does not significantly influence financial profitability performance. However, to increase profitability, Islamic banks in Indonesia suggested conducting CSR practices focusing on Legal, Economic, and Philanthropic dimensions. Meanwhile, the Environment and Ethical dimensions need to be adjusted to influence the profitability of a bank.Keywords: Corporate Social Responsibility, Corporate Social Responsibility Disclosure, Financial Performance, Profitability, Islamic Banking, Indonesia